Hot corrosion behaviour of different Cr3C2–NiCr coatings on boiler tube steel at elevated temperature. (25th June 2019) - Singh, Karanjit; Goyal, Khushdeep; Goyal, Rakesh
Abstract : Purpose: This paper aims to investigate hot corrosion behaviour of different Cr3 C2 –NiCr coatings on boiler tube steel. Design/methodology/approach: High velocity oxy fuel technique has been used to deposit different coatings on commercially available ASTM-SA213-T22 boiler tube steel. The hot corrosion studies have been performed in molten salt environment at 900°C temperature in silicon tube furnace in laboratory. Findings: The results showed that uncoated superalloy suffered intense spalling and the weight change was massive during each cycle on studies of hot corrosion 900°C. The 100 per cent NiCr and 10 per cent (Cr3 C2 ) – 90 per cent (NiCr) coatings provided better protection to T22 steel against the hot corrosion because of the formation of Ni and Cr3 C2 layers. Originality/value: In this research a variety of coatings have been used. This research work has been aimed to investigate the hot corrosion behavior of Boiler Steel b with different Cr3 C2 –NiCr coatings, under molten salt environment in Silicon tube furnace at 900°C, under cyclic conditions.